2019
DOI: 10.3389/fmolb.2019.00090
|View full text |Cite
|
Sign up to set email alerts
|

2-Deoxyglucose and Newcastle Disease Virus Synergize to Kill Breast Cancer Cells by Inhibition of Glycolysis Pathway Through Glyceraldehyde3-Phosphate Downregulation

Abstract: Targeting cancer cells metabolism is promising strategy in inhibiting cancer cells progression that are known to exhibit increased aerobic glycolysis. We used the glucose analog 2-Deoxyglucose (2-DG) as a competitor molecule of glucose. To further enhance the effectiveness of 2-DG, the Newcastle disease virus (NDV) was used as a combination virotherapy to enhance the anti-tumor effect. Human and mouse-breast cancer cells were treated by NDV and/or 2-DG. The effect was analyzed by study cell viability, apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 42 publications
(52 reference statements)
4
30
0
1
Order By: Relevance
“…The abnormality of aerobic glycolysis is considered as one of the tumor markers, and in BC, aerobic glycolysis can not only provide nutrition for cell proliferation but also help to promote cell proliferation and metastasis. 22 A previous study revealed that histone methyltransferase Set8 could regulate aerobic glycolysis by stabilizing HIF1α. 23 In our study, we also found that the inhibition of PRMT5 expression significantly suppressed the aerobic glycolysis of BCCs, which was the first time we found that PRMT5 could affect it of BCCs.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormality of aerobic glycolysis is considered as one of the tumor markers, and in BC, aerobic glycolysis can not only provide nutrition for cell proliferation but also help to promote cell proliferation and metastasis. 22 A previous study revealed that histone methyltransferase Set8 could regulate aerobic glycolysis by stabilizing HIF1α. 23 In our study, we also found that the inhibition of PRMT5 expression significantly suppressed the aerobic glycolysis of BCCs, which was the first time we found that PRMT5 could affect it of BCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 2-DG induces apoptosis of neuroblastoma SK-N-BE (2) cells [ 176 ] and its chronic dietary administration inhibits tumor incidence in a mouse model of hepatocarcinogenesis [ 177 ]. Moreover, 2-DG synergizes with Newcastle disease virus to kill breast cancer cells to inhibit GA-3-P dehydrogenase [ 178 ], and increases the efficacy of Adriamycin and paclitaxel in human osteosarcoma and non-small cell lung cancers in vivo [ 179 ].…”
Section: The Warburg Effect and Tumor Therapymentioning
confidence: 99%
“…It was also found that YAP1 is genetically controlled in rat liver cancer and determines the fate and stem-like behavior of the human disease [ 182 ]. YAP increases glycolysis [ 179 ] and supports the expression of Glut3, a known driver of a cancer stem cell phenotype, whose expression is elevated in cancer [ 18 , 182 ]. YAP/TAZ/TEAD and AP-1 form a complex that synergistically activates target genes controlling S-phase entry and mitosis [ 183 ].…”
Section: The Warburg Effect and Tumor Therapymentioning
confidence: 99%
“…Furthermore, pyruvate dehydrogenase kinase inhibition showed to improve reovirus oncolytic anti-tumor efficacy in several cancer types [29]. We reported previously that 2DG would enhance oncolytic NDV against breast cancer cells through glycolysis inhibition by downregulation of glyceraldehyde3-phosphate (GAPDH) [30]. Here, we investigate using D-Mannoheptulose, a hexokinase inhibitor to increase breast cancer cells sensitivity to oncolytic NDV, and the proposed mechanisms of this combination using glycolysis products analysis in breast cancer cells NDV-mediated oncolysis correlates with the disturbance within the metabolism.…”
Section: Introductionmentioning
confidence: 99%